Current Status of Cardiovascular Imaging in Germany: Structured Data from the National Certification Program, ESCR Registry, and Survey among Radiologists - Sieren, Malte Maria; Maintz, David; Gutberlet, Matthias; Krombach, Gabriele Anja; Bamberg, Fabian; Hunold, Peter; Lehmkuhl, Lukas; Fischbach, Katharina; Reinartz, Sebastian; Antoch, Gerald; Barkhausen, Jörg; Sandstede, Jörn; Völker, Martin; Naehle, Claas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose In the light of the increasing importance of cardiovascular cross-sectional imaging in current guidelines, the goal of this study is to provide a comprehensive overview of cardiovascular imaging (CVI) offered by radiological institutions across Germany.Materials and Methods Data were extracted from the national certification program database of the German Roentgen Society (DRG) from 2015–2021. A nationwide online survey among radiology institutes (university hospitals, non-university hospitals, and private practices) was conducted for 2019, and data was extracted from the European Society of Cardiovascular Radiology (ESCR) registry. The data collection's key points included the number of centers and individuals certified for CVI, the number of cardiac CT and MRI examinations performed, the reporting habits, and the participation in the ESCR registry.Results 71 centers and 1278 persons, both with a substantial increase since 2015, were registered and certified by the DRG to perform CVI. According to the survey, a total of 69,286 CT and 64,281 MRI examinations were performed annually. Data from the survey and the ESCR registry indicated that reporting was mostly done solely by radiologists or, to a lesser degree, in joint consensus meetings with non-radiologists. The overall participation rate in the ESCR registry was 48 % among the surveyʼs participants.Conclusion This comprehensive analysis demonstrates that high-quality CVI by radiologists is available nationwide. The current challenges are to provide the best medical and technical quality of CVI by radiology for patient care and to ensure economic sustainability in the German health care system to accommodate the predicted substantial need for CVI in the future.Key Points Citation Format
Keywords: cardiovascular imaging; ESCR Registry; survey; quality assessment; certification program